GENDER ASPECTS OF ENGLISH AND UZBEK LANGUAGE - Agzamova Dildora; To'ychiyeva Madina Akmaljon qizi (Western European Studies, 2024)
This article explores the gender aspects present in the English and Uzbek languages, shedding light on the linguistic features that reflect and shape gender roles in these two distinct linguistic systems. The study employs a comparative analysis to investigate how cultural and social factors influence language, contributing to the construction of gender identities. Through a comprehensive examination of linguistic elements, this research aims to deepen our understanding of the intricate relationship between language and gender, providing valuable insights for linguists, educators, and policymakers
Keywords: Language and gender; linguistic features; sociolinguistics